Swine Interferon-Inducible Transmembrane Proteins Potently Inhibit African Swine Fever Virus Replication - Cai, Siqi; Zheng, Zezhong; Cheng, JiaoJiao; Zhong, Lintao; Shao, Ran; Zheng, Feiyan; Lai, Zhiying; Ou, Jiajun; Xu, Liang; Zhou, Pei; Lu, Gang; Zhang, Guihong (Frontiers in Immunology, 2022)
African swine fever virus (ASFV) causes an acute, hemorrhagic, and highly contagious disease in domestic swine, leading to significant economic losses to the global porcine industry. Restriction factors of innate immunity play a critical in host antiviral action. However, function of swine restriction factors of innate immunity on ASFV has been seldomly investigated. In this study, we determined five homologues of swine interferon-induced transmembrane proteins (SwIFITM [named SwIFITM1a, -1b, -2, -3, and -5]), and we found that they all exhibit potent antiviral activity against ASFV. Expression profile analysis indicated that these SwIFITMs are constitutively expressed in most porcine tissues. Whether infected with ASFV or treated with swine interferon, the expression levels of SwIFITMs were induced in vitro. The subcellular localization of SwIFITMs was similar to that of their human homologues. SwIFITM1a and -1b localized to the plasma membrane, SwIFITM2 and -3 focused on the cytoplasm and the perinuclear region, while SwIFITM5 accumulated in the cell surface and cytoplasm. The overexpression of SwIFITM1a, -1b, -2, -3, or -5 could significantly inhibit ASFV replication in Vero cells, whereas knockdown of these genes could enhance ASFV replication in PAMs. We blocked the constitutive expression of endogenous IFITMs in Vero cells using a CRISPR-Cas9 system and then infected them with ASFV. The results indicated that the knockout of endogenous IFITMs could enhance ASFV replication. Finally, we expressed five SwIFITMs in knockout Vero cell lines and then challenged them with ASFV. The results showed that all of the SwIFITMs had a strong antiviral effect on ASFV. This research will further expand the understanding of the anti-ASFV activity of porcine IFITMs.